CELIBACY AS SOCIAL COUNTER-CONDUCT PRACTICE IN EARLY CHURCH - Tumanan, Perdian Koeswanto Magelhaens (QUAERENS: Journal of Theology and Christianity Studies, 2022)
This paper argues that the concept of sexual abstinence in early Christianity was not based on biblical proof-texting, but rather resulted from constructive theological efforts in response to the socio-political reality of the time and the early Christians’ aspirations towards women and the marginalized. By exploring the discourse surrounding marriage and sexuality in the Greco-Roman world and its impact on early Christianity, this paper highlights how the teaching on sexual abstinence challenged the imperial philosophy of desire and control. The paper posits that celibacy and sexual abstinence served as a social counter-conduct practice in response to the little appreciation for women’s bodies and the marginalized. In short, the teaching of Christian chastity addressed the elitism that pervasive in Greco-Roman philosophy of marriage and sexuality. Ultimately, the debate about celibacy in early Christianity was about the nature of human solidarity.